PERTANGGUNGJAWABAN PERUSAHAAN INDUK SEBAGAI CORPORATE GUARANTEE TERHADAP ANAK PERUSAHAAN TERKAIT ADANYA PEMBERIAN FASILITAS KREDIT INVESTASI OLEH PERBANKAN - Priawan Harmasandi; Bismar Nasution; Keizerina Devi (Universitas Sumatera Utara, 2015)
PERTANGGUNGJAWABAN PERUSAHAAN INDUK SEBAGAI CORPORATE GUARANTEE TERHADAP ANAK PERUSAHAAN TERKAIT ADANYA PEMBERIAN FASILITAS KREDIT INVESTASI OLEH PERBANKAN Priawan Harmasandi Raharjo[1] Bismar Nasution[2] Keizerina Devi Azwar[3] ABSTRACT One which becomes the capital source for subsidiaries namely using their banking credit facilities. But, banks need a guarantee which may give trust and certainty to them to be able to receive their money back in the event of bad debts of the subsidiaries credit. Moreover, credit asked by the subsidiaries is an investment bank credit that categorized as a big one. One who can be credit guarantees for subsidiaries is the parent company. Therefore, the legal act will certainly give legal effects on its own. It becomes a background in writing of this thesis that are to find out the settings guarantee credit banking in Indonesia, to find out legal relationship between parent company and subsidiaries in terms of guarantee in Indonesia, and to find out the accountability of parent company as corporate guarantee to subsidiaries related to the granting of credit facilities by investment banking. Methods used in writing the thesis is normative legal research (juridical normative) because this research done by means of analyzing law written in library materials or secondary data and reference materials in the field of law. Based on the results of the normative legal research (juridical normative) noted that credit guarantee arrangements banking in Indonesia that is generally found in the article 1131 of Book of Civil Law Legislation and also found in Act No. 10 in 1998 about the Changes Of Act No.7 in 1992 On Banking which in the Act is better known as the collateral. The legal relationship that exists between a parent company and its subsidiaries in terms of guarantee in Indonesia is the parent company can provide corporate guarantee for its subsidiaries. The accountability of parent company as corporate guarantee of subsidiaries related to the granting of credit facilities by investment banking, namely that the parent company is fully responsible for the subsidiary's credit. [1] Students of Law Faculty University of Sumatera Utara [2] Supervisor I, Lecturer of Law Faculty University of Sumatera Utara [3] Supervisor II, Lecturer of Law Faculty University of Sumatera Utara